Pengaruh Partisipasi Penyusunan Key Performance Indicator (KPI) Terhadap Komitmen Pencapaian Sasaran Kerja Karyawan Di Pt. Xyz, Yogyakarta - Rislisa, Rislisa; Himam, Fathul (Jurnal Psikologi, 2015)
Providing information about the reasons and rationale of why a set of purpose is considered important and the participation in setting the work purpose serve as important factors to improve employees’ work commitment to the goal. This study was aimed to determine the effect of participation in setting the key performance indicator (KPI) to increase the commitment for achievement of work objectives in PT. XYZ. There were 36 subjects involved in this research, which consisted of 18 individuals assigned randomly as experimental group and 18 individuals as control group. The design of this experimental research was pretest-posttest control group design. KPI preparation participation treatment was given to the experimental groups and the control groups did not receive treatment. ANOVA analysis was use to analyze the data. This research indicated, that there was no significant effect of participation in setting Key Performance Indicator (KPI) on work goals commitment. (F = .425; p>.05). On the other hand, this research found a tendency that commitment could increase knowledge and subjects’ understanding in how to achieve work goals.